Excited States Mapped by Secondary Photoemission - Bovet, M.; Strocov, V. N.; Clerc, F.; Koitzsch, Christian; Naumovic, D.; Aebi, Philipp (My University, 2004)
We report on angle-resolved photoemission (ARPES) experiments on Cu(110) using Mg Kα radiation. The secondary emission (SE) fine structure of electrons below 50 eV is found to map the empty band structure relevant for absolute band mapping in ARPES. The finding is based on a direct comparison of our experiments with very low-energy electron diffraction data [Phys. Rev. Lett. 81, 4943 (1998)] recently shown to map the unoccupied states representing the photoemission final-state. This suggests a new theoretical approach to the SE process treating the outgoing electron state as the time-reversed diffraction state.